GAMBARAN KUALITAS HIDUP LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS RENDANG PADA PERIODE 27 FEBRUARI SAMPAI 14 MARET 2015 - Sri Santiya Anbarasan (DiscoverSys Inc., 2015)
OUTLOOK ON QUALITY OF LIFE OF ELDERLY WITH HYPERTENSION IN PUSKESMAS RENDANG AREA DURING PERIOD 27 FEBRUARY TO 14 MARCH 2015ABSTRACTBackground: Hipertension is one of the biggest health problem faced in the world, especially in developing countries. According to data from Bali Province Health Service, patients suffering from hipertension in Bali in 2010 accounts to 8837 people. Whereas total visit of elderly with hypertension in 2013 sums up to 1354, which is 9,41% from total cases that visited Puskesmas Rendang in 2013. High number of hypertension cases especially in elderly affects their quality of life.Aim: To know the quality of life of elderly suffering from hypertension.Method: The type of study is descriptive quantitative. Study was conducted in elderly posyandu in Puskesmas Rendang, Karangasem district during period of 27 February till 14 March 2015. Sample was obtained through consecutive sampling technique with a total sample of 60 people. Instrument used in the form of questionnaire which was created by WHO that is World Health Organization Quality Of Life – Bref (WHOQOL-BREF). Data analysis technique used was univariate analysis and bivariate analysis.Result: Quality of life of elderly is generally good (58.3%), physical health quality of elderly is bad (71.7%), psychological quality is good (61.7%), personal social quality is not too influential (50.0%), and environment quality is bad (73.3%).Conclusion: Quality of life in elderly with hypertension is generally good, only physical health quality and environment quality is bad.